Utilization of ionic liquids as compatibilizing agents for polymer blends-preparations and properties - Shamsuri, Ahmad Adlie; Abdan, Khalina; Md. Jamil, Siti Nurul Ain (Taylor and Francis Group, 2023)
Recently, ionic liquids have been utilized to compatibilize polymer blends. In this brief review, two types of ionic liquids utilized as compatibilizing agents for polymer blends are described, namely imidazolium-based and phosphonium-based ionic liquids. Additionally, the preparation of polymer blends with different processes is presented. The effects of ionic liquids as compatibilizing agents on the chemical, mechanical, and thermal properties of polymer blends are also briefly reviewed. The information presented in this review contributes to a better understanding of the preparation of polymer blends compatibilized with ionic liquids and the crucial properties of polymer blends.